Design and Rationale of Routine UltrasouNd GuIdance for Vascular AccEss foR Cardiac Procedures: A Randomized TriaL (UNIVERSAL) - Sulaiman Alrashidi, MD; Marc-André d’Entremont, MD, MPH; Omar Alansari, MD; Jose Winter, MD; Bradley Brochu, MD; Laura Heenan, MSc; Elizabeth Skuriat, MSc; Jessica Tyrwhitt, BSc; Michael Raco, MD; Michael B. Tsang, MD, MSc; Nicholas Valettas, MD, MASc; James Velianou, MD; et al. (CJC Open, 2022)
Background: A significant limitation of femoral artery access for cardiac interventions is the increased risk of vascular complications and bleeding compared to radial access. Ultrasound (US)-guided femoral access may reduce major vascular complications and bleeding. We aim to determine whether routinely using US guidance for femoral arterial access for coronary angiography or intervention will reduce Bleeding Academic Research Consortium (BARC) 2, 3, or 5 bleeding or major vascular complications. Methods: The Ultrasound Guidance for Vascular Access for Cardiac Procedures: A Randomized Trial (UNIVERSAL) is a multicentre, prospective, open-label, randomized trial with blinded outcomes assessment. Patients undergoing coronary angiography with or without intervention via a femoral approach with fluoroscopic guidance will be randomized 1:1 to US-guided femoral access, compared to no US. The primary outcome is the composite of major bleeding based on the BARC 2, 3, or 5 criteria or major vascular complications within 30 days. The trial is designed to have 80% power and a 2-sided alpha level of 5% to detect a 50% relative risk reduction for the primary outcome based on a control event rate of 14%. Results: We completed enrollment on April 29, 2022, with 621 randomized patients. The patients had a mean age of 71 years (25.4% female), with a high rate of comorbidities, as follows: 45% had a prior percutaneous coronary intervention; 57% had previous coronary artery bypass surgery; and 18% had peripheral vascular disease. Conclusions: The UNIVERSAL trial will be one of the largest randomized trials of US-guided femoral access and has the potential to change guidelines and increase US uptake for coronary procedures worldwide. Résumé: Introduction: Par rapport à l’abord radial, la limitation importante de l’abord artériel fémoral lors des interventions au cœur pose un risque accru de complications vasculaires et de saignements. L’abord fémoral guidé par ultrasons (US) peut contribuer à réduire les complications vasculaires majeures et les saignements. Nous avons pour objectif de déterminer si l’utilisation systématique du guidage par US pour l’abord artériel fémoral lors des angiographies ou des interventions coronariennes contribuera à réduire les saignements de type 2, 3 ou 5 selon le Bleeding Academic Research Consortium (BARC) ou les complications vasculaires majeures. Méthodes: L’Ultrasound Guidance for Vascular Access for Cardiac Procedures: A Randomized Trial (UNIVERSAL) est un essai multicentrique, prospectif, ouvert, à répartition aléatoire, réalisé par une évaluation à l’insu des résultats. Les patients subissant une angiographie coronarienne avec ou sans intervention par voie fémorale sous guidage fluoroscopique seront répartis de façon aléatoire 1:1 à l’abord fémoral guidé par US ou sans US. Le principal critère d’évaluation est le critère composite de saignements majeurs de type 2, 3 ou 5 selon les critères du BARC ou de complications vasculaires majeures dans les 30 jours. L’essai est conçu de façon à avoir une puissance de 80 % et un seuil alpha bilatéral de 5 % pour déterminer la réduction du risque relatif de 50 % du critère d’évaluation principal selon un taux d’événements dans le groupe témoin de 14 %. Résultats: Le 29 avril 2022, nous avons terminé le recrutement de 621 patients choisis aléatoirement. Les patients avaient un âge moyen de 71 ans (25,4 % de femmes) et un taux élevé de comorbidités : 45 % avaient déjà subi une intervention coronarienne percutanée, 57 % avaient déjà subi un pontage aorto-coronarien et 18 % avaient une maladie vasculaire périphérique. Conclusions: L’essai UNIVERSAL qui sera l’un des plus vastes essais à répartition aléatoire sur l’abord fémoral guidé par US a le potentiel de faire changer les lignes directrices et de faire augmenter le recours aux US lors des interventions coronariennes dans le monde entier.